2013
DOI: 10.4049/jimmunol.1201393
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Negative Cross-Talk between Liver X Receptors (LXRs) and STAT1: Effects on IFN-γ–Induced Inflammatory Responses and LXR-Dependent Gene Expression

Abstract: Liver X receptors (LXRs) exert key functions in lipid homeostasis and in control of inflammation. In this study we have explored the impact of LXR activation on the macrophage response to the endogenous inflammatory cytokine IFN-γ. Transcriptional profiling studies demonstrate that ∼38% of the IFN-γ–induced transcriptional response is repressed by LXR activation in macrophages. LXRs also mediated inhibitory effects on selected IFN-γ–induced genes in primary microglia and in a model of IFN-γ–induced neuroinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 55 publications
1
37
1
Order By: Relevance
“…A role for coactivator redistribution or squelching has been previously suggested to explain transcriptional repression by NRs, but most of those studies were performed using transfection to overexpress receptors or coactivators and used reporter genes as readouts (Kamei et al 1996;Fronsdal et al 1998;Lee et al 2000;Li et al 2000;Kim et al 2001;Zhang and Teng 2001;Manna and Stocco 2007;He et al 2012;Pascual-Garcia et al 2013). This model gained further support recently with evidence that the endogenous coactivator NCOA3 is lost from sites of diminished DNase I hypersensitivity upon E2 hormone treatment in MCF-7 cells (He et al 2012).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A role for coactivator redistribution or squelching has been previously suggested to explain transcriptional repression by NRs, but most of those studies were performed using transfection to overexpress receptors or coactivators and used reporter genes as readouts (Kamei et al 1996;Fronsdal et al 1998;Lee et al 2000;Li et al 2000;Kim et al 2001;Zhang and Teng 2001;Manna and Stocco 2007;He et al 2012;Pascual-Garcia et al 2013). This model gained further support recently with evidence that the endogenous coactivator NCOA3 is lost from sites of diminished DNase I hypersensitivity upon E2 hormone treatment in MCF-7 cells (He et al 2012).…”
Section: Discussionmentioning
confidence: 81%
“…Support for this coactivator competition model, often referred to as squelching, has been largely based on TF overexpression experiments in transfection systems (Gill and Ptashne 1988;Kelleher et al 1990; Kamei et al 1996;Fronsdal et al 1998;Lee et al 2000;Li et al 2000;Kim et al 2001;Zhang and Teng 2001;Manna and Stocco 2007;He et al 2012;Pascual-Garcia et al 2013), although a recent study demonstrated coactivator redistribution with endogenous factors and chromatin on a genome-wide scale in the context of E2-treated MCF-7 cells (He et al 2012).…”
mentioning
confidence: 99%
“…Moreover, a later study showed that mutant forms of both LXRs lacking SUMO acceptor sites (LXR α K328R/K434R and LXR β K410R/K448R) (Fig. 1) have a decreased capacity to prevent the binding of the proinflammatory signal transducer and activator of transcription 1 transcription factor to the Nos2 promoter (59), further establishing the importance of LXR SUMOylation on its transrepressive capacity. However, this transrepression model has now been challenged.…”
Section: Posttranslational Modifications Of Nrsmentioning
confidence: 86%
“…In cultured macrophages, peroxisome proliferator-activated receptor-gamma (PPAR-γ) and LXRs have been found to be SUMOylated, which regulates the transrepression of inflammatory response genes [50]. SUMOylation is usually associated with a cytoprotective response to cellular stressors.…”
mentioning
confidence: 99%